The Role Of Household Characteristics And Regional Transportation In Trip Generation In Semi-Rural Areas Of North Toraja - Yulius Pakiding; Azril Tangke Sombolinggi; Rilva Toding Bua'; Abdias Tandy Arrang (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2026)
This study aims to analyze household trip generation in semi-rural areas of North Toraja based on household characteristics and regional transportation conditions. The study was conducted in Pangli and Sa'dan Matallo located along the Rantepao–Sa’dan provincial road corridor. This research employed a quantitative approach using a survey method with 181 household respondents. Data analysis was carried out using descriptive analysis, binary logistic regression, and Chi-Square analysis with the assistance of IBM SPSS Statistics software. The results indicate that vehicle ownership and number of family members significantly influence the probability of household trip generation, with significance values of 0.006 and 0.000, respectively. Meanwhile, household income does not significantly affect household trip generation categories. The Chi-Square analysis shows that travel time has a significant relationship with trip generation categories with a significance value of 0.033, while transportation mode and travel distance do not show significant relationships. In addition, regional transportation characteristics indicate an increase in population and motor vehicle growth in North Toraja Regency from 2021 to 2024, with a coefficient of determination value of , indicating a very strong relationship between population growth and motor vehicle growth. The findings suggest that household trip generation in semi-rural areas is influenced by a combination of household socio-economic characteristics, regional development, and transportation conditions. This study is expected to provide recommendations for regional transportation planning and mobility management in semi-rural areas.